2020
DOI: 10.1016/j.celrep.2020.107525
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Profiling Identifies DNA Methylation Signatures of Aging in Rod Photoreceptors Associated with Alterations in Energy Metabolism

Abstract: Highlights d WGBS identifies 2,054 differentially methylated regions (DMRs) in aging mouse rods d DMRs are present in regulatory regions and cluster at chromosomal hotspots d DMRs are linked to dysregulation of aging pathways and energy metabolism d Old retinas exhibit lower basal respiration and higher fatty acid dependency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 91 publications
(125 reference statements)
1
19
0
Order By: Relevance
“…Beyond that, PRPH2, CDHR1, ABCA4, and GUCA1A were downregulated in a mouse knockout model of NEUROD1 (Neuronal Differentiation 1) gene ( Ochocinska et al, 2012 ). Perturbations in the transcription factors ONECUT2 (One Cut Homeobox 2) , EGR1 (Early Growth Response 1) , NRL (Neural Retina Leucine Zipper), and VAX2 (Ventral Anterior Homeobox 2) seems to affect the expression of the genes found in association with CACD in this review, all based in knockout assays in mouse ( Alfano et al, 2011 ; Goetz et al, 2014 ; Oh et al, 2017 ; Han et al, 2018 ; Corso-Díaz et al, 2020 ). MECP2 (Methyl-CpG-Binding Protein 2) was also included in this group but is the unique factor not associated with retinal diseases or eye development, playing a substantial role in early neurodevelopment ( Urdinguio et al, 2008 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Beyond that, PRPH2, CDHR1, ABCA4, and GUCA1A were downregulated in a mouse knockout model of NEUROD1 (Neuronal Differentiation 1) gene ( Ochocinska et al, 2012 ). Perturbations in the transcription factors ONECUT2 (One Cut Homeobox 2) , EGR1 (Early Growth Response 1) , NRL (Neural Retina Leucine Zipper), and VAX2 (Ventral Anterior Homeobox 2) seems to affect the expression of the genes found in association with CACD in this review, all based in knockout assays in mouse ( Alfano et al, 2011 ; Goetz et al, 2014 ; Oh et al, 2017 ; Han et al, 2018 ; Corso-Díaz et al, 2020 ). MECP2 (Methyl-CpG-Binding Protein 2) was also included in this group but is the unique factor not associated with retinal diseases or eye development, playing a substantial role in early neurodevelopment ( Urdinguio et al, 2008 ).…”
Section: Resultsmentioning
confidence: 90%
“…TTLL5 is expressed primarily in the testis and in the inner part of photoreceptors of the retina, in the base of the photoreceptor’s primary cilium ( Bedoni et al, 2016a ). Few recent associations with cone-rod dystrophies, including one that reports a TTLL5 multi-exon ( Reig et al, 1995a ; Hoyng et al, 1996b ; Kohl et al, 1997b ; Payne et al, 1998 ; Urdinguio et al, 2008 ; Alfano et al, 2011 ; Ochocinska et al, 2012 ; Goetz et al, 2014 ; Oh et al, 2017 ; Han et al, 2018 ; Corso-Díaz et al, 2020 ) deletion that causes cone-rod dystrophy, were found in a retrospective study with Arab families ( Westermann and Weber, 2003 ; Sergouniotis et al, 2014 ; Bedoni et al, 2016b ; Sun et al, 2016 ; Dias et al, 2017 ; Méjécase et al, 2020 ). Photoreceptors of mice with truncated alleles of TLL5 or of the Retinitis pigmentosa GTPase regulator ( RPGR ) gene exhibit no tubulin glutamylation (addition of glutamate molecules).…”
Section: Discussionmentioning
confidence: 99%
“…The msPIPE was applied to publicly-available human (accession number: PRJEB28044) [ 49 ] and mouse (accession number: PRJNA556668) WGBS datasets [ 50 ] (Additional file 2 : Table S1). The human dataset was generated from the pooled libraries of DNA obtained from the blood and sperm of six young men (18–24 years) and six old men (61–71 years), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These so called “hotspots” of differential DNA methylation could suggest loci in these regions are prone to epigenetic alterations including methylation. Transposable elements (TEs) tend to be heavily methylated and have been reported to have involvement in developmental processes in almond, such as the juvenile-to-adult transition (Han et al ., 2018; Corso-Díaz et al ., 2020; Wyler et al ., 2020), suggesting the “hotspots” identified in almond in this study could contain TE sequences. This type of pattern has been documented in other species such as rice, were a study on salt tolerance identified DMRs that tended to cluster on specific chromosomes and were typically associated with TEs on these chromosomes (Ferreira et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%